(untitled) (Diametros, 2014)
The aim of the paper is to present and analyze the interpretation of the Enlightenment which has recently been proposed by Jonathan Israel, with the focus on its philosophical aspect as opposed to the historical one. The paper consists of two parts. The task of the first part is reconstructive: it attempts to explore Israel’s most characteristic statements concerning the Enlightenment. The second and more extensive part has a polemical character: it endeavours to furnish the reader with an answer to the question of the degree to which the understanding of the Enlightenment proposed by Israel can be considered a satisfying interpretation of this period. The paper suggests that the main problem which may undermine Israel’s account of the Enlightenment is associated with the unduly selective interpretation of Spinoza’s philosophy and its position in the intellectual society of that time.